Long-term outcomes of Fine Needle Diathermy for established corneal neovascularisation. Issue 4 (23rd January 2014) - Trikha, S; Parikh, S; Osmond, C; Anderson, D F; Hossain, P N
Abstract : Background/aims: Corneal neovascularisation (CoNV) can lead to significant ocular comorbidity with reduction in vision and cosmesis. A number of techniques have been described to reduce CoNV, but these can be expensive. Our study aimed to determine the safety, efficacy and long-term outcomes of fine needle diathermy (FND) for CoNV. Methods: A 5-year retrospective study identified all cases of FND. Indications, intraoperative complications, and postoperative visual acuity, after treatment and retreatments, were documented, along with the procedure time. Evidence of regression and number of retreatments were identified. Results: 56 eyes from 52 patients underwent FND for CoNV. The main indications included herpes simplex keratitis (HSK) (53%, n=25) and microbial keratitis/peripheral ulcerative keratitis (13%, n=6). Pretreatment acuity was significantly correlated with extent of CoNV (p=0.044). One complication was noted during the procedure—an intrastromal and subconjunctival haemorrhage (rate 2%). 68.1% of patients demonstrated regression at first follow-up (mean 6.9 weeks), and 89.3% (n=42) showed regression with two or less treatments. Mean post-FND acuity was 0.72 (range −0.2–3.0) vs 0.82 (−0.2–3.0) preprocedure (p=0.08). VA improved in the HSK subgroup (p=0.012). Mean follow-up was 18.9 months (range 1–56 months). Conclusions: In the largest case series reported, FND appears to be a safe and effective technique in the long term to induce regression of CoNV, with significant improvement in the VA of patients with HSK.